Types of Metaphor and Problems of Translation - Khayrullayeva Nodira Nematilloyevna (Universitas Muhammadiyah Sidoarjo, 2022)
This article proposes a framework of studying metaphorical terms in the sphere of economics, in the context of translation difficulties lying in the base of their different perception in English and in Russian. In order to make an accurate translation, it is very important to identify the types of transformations used in the translation of English metaphorical terms in the field of economics, into the Uzbek language. The following tasks should be fulfilled in the process of research:(1) to identify semantic and pragmatic characteristics of metaphorical economic terms; (2) to define types of transformations used in translation of metaphorical economic terms.